Imaging Tips and Tricks in Management of Renal and Urothelial Malignancies - Sanyal, Shanti Ranjan; Arora, Ankur; Nisreen, Amin; Mohamed, Khattab; Mohammad, Saeed Kilani; Baruah, Deb (Indian Journal of Radiology and Imaging, 2022)
Management of urological malignancies has evolved significantly with continually changing guidelines and treatment options which demand more centralized involvement of radiology than ever before.Radiologists play a pivotal role in interpreting complex cancer scans and guiding clinical teams toward the best management options in the light of clinical profile. Management of complex uro-oncology cases is often discussed in multidisciplinary meetings which are essential checkpoints to evaluate an overall picture and formulate optimal treatment plans.The aim of this article is to provide a radiological perspective with practical guidance to fellow radiologists participating in uro-oncology multidisciplinary meetings based on commonly encountered case scenarios, updated guidelines, and cancer pathways.Crucial imaging tips with regards to renal and urinary tract cancers, upon which therapeutic decisions are made, have been condensed in this article after reviewing several complex cases from urology multidisciplinary meetings and European Association of Urology guidelines.Outline of various diagnostic and management strategies, key staging features, surveillance guidelines, and, above all, what the onco-urologists want to know from radiologists have been succinctly discussed in this article.
Keywords: renal masses; urinary tract; imaging tips; surveillance; management